2020
DOI: 10.1016/j.neurobiolaging.2019.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological alterations in the nucleus reuniens of a mouse model of Alzheimer's disease

Abstract: Alterations in the neurophysiology of hippocampal and cortical neurons has been linked to network hyperexcitability in mouse models of amyloidopathy.  The nucleus reuniens (Re) is part of a cognitive network involving the hippocampal formation and prefrontal cortex. Increased cellular activity in Re has been linked to the generation of hippocampal-thalamo-cortical seizure activity in J20 mice.  Re neurons display hyperpolarised resting membrane potentials in J20 mice. Passive membrane properties are unaffect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 50 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…10,[14][15][16] Walsh found that nucleus reuniens of a mouse model of Alzheimer's disease exhibited an increased propensity to rebound burst following hyperpolarizing current stimuli, and this may contribute to hippocampalthalamo-cortical hyperexcitability. 17 In the peripheral nervous system (PNS), a small number of low-threshold mediumsized dorsal root ganglia (DRG) neurons also generate RF. 18,19 In neuropathic pain conditions, DRG neurons become hyperexcitable after DRG injury.…”
Section: Introductionmentioning
confidence: 99%
“…10,[14][15][16] Walsh found that nucleus reuniens of a mouse model of Alzheimer's disease exhibited an increased propensity to rebound burst following hyperpolarizing current stimuli, and this may contribute to hippocampalthalamo-cortical hyperexcitability. 17 In the peripheral nervous system (PNS), a small number of low-threshold mediumsized dorsal root ganglia (DRG) neurons also generate RF. 18,19 In neuropathic pain conditions, DRG neurons become hyperexcitable after DRG injury.…”
Section: Introductionmentioning
confidence: 99%